2019
DOI: 10.1002/ijc.32036
|View full text |Cite
|
Sign up to set email alerts
|

miR‐4324‐RACGAP1‐STAT3‐ESR1 feedback loop inhibits proliferation and metastasis of bladder cancer

Abstract: Considering the importance of microRNAs (miRNAs) in regulating cellular processes, we performed microarray analysis and revealed miR‐4324 as one of the most differentially expressed miRNAs in bladder cancer (BCa). Then, we discovered that miR‐4324 was a negative regulator of Rac GTPase activating protein 1 (RACGAP1) and that RACGAP1 functioned as an oncogenic protein in BCa. Our studies indicated that ectopic overexpression of miR‐4324 in BCa cells significantly suppressed cell proliferation and metastasis and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
41
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 53 publications
(42 citation statements)
references
References 38 publications
1
41
0
Order By: Relevance
“…miR-4324 has been demonstrated to be abnormally expressed in several human cancers and to function as a tumor suppressor. [8][9][10][11] In this study, we showed that miR-4324 expression was reduced in CRC tissues and cell lines compared with normal tissues and cell line. We also showed that overexpression of miR-4324 inhibited CRC cell growth, migration, and invasion.…”
Section: Discussionmentioning
confidence: 63%
“…miR-4324 has been demonstrated to be abnormally expressed in several human cancers and to function as a tumor suppressor. [8][9][10][11] In this study, we showed that miR-4324 expression was reduced in CRC tissues and cell lines compared with normal tissues and cell line. We also showed that overexpression of miR-4324 inhibited CRC cell growth, migration, and invasion.…”
Section: Discussionmentioning
confidence: 63%
“…Knocking out RACGAP1 in hepatocellular carcinoma cells hampered cytokinesis and induced cell apoptosis [38]. Upregulated RACGAP1 predicted the poor outcomes in patients with hepatocellular carcinoma [38], ovarian cancer [39], and bladder cancer [40]. However, there are no preclinical or clinical studies demonstrating the role of RACGAP1 in LUAD.…”
Section: Discussionmentioning
confidence: 99%
“…18 To monitoring the recurrence and progression of BCa, the patients had to undergo cystoscopy after surgery, which will bring a huge mental and economic burden to the patient. [21][22][23] These biomarkers may contribute to the prediction of prognosis for BCa patients. [21][22][23] These biomarkers may contribute to the prediction of prognosis for BCa patients.…”
Section: Discussionmentioning
confidence: 99%
“…19,20 Our group has previously found some biomarkers related to BCa prognosis and carcinogenesis. [21][22][23] These biomarkers may contribute to the prediction of prognosis for BCa patients. Nevertheless, a single biomarker lacks sufficiently accuracy and effectiveness, the comprehensive methods combined several biomarkers can significantly improve the accuracy and effectiveness.…”
Section: Discussionmentioning
confidence: 99%